Gender and Race in the Gaming World - Nakamura, Lisa (Society and the Internet : how networks of information and communication are changing our lives, 2019)
Age is not alone in shaping real and imagined differences in Internet use. Racial and gender-based stereotypes abound and need to be empirically challenged. This chapter explores the relationships between race, gender, sexuality, and digital cultures in one increasingly significant digital domain—gaming. With a review of previous scholarship on race, gender, and gaming, the author shows that we see few signs of a “post-racial” society being brought into being. In fact, gaming is a digital activity where racism and sexism are commonplace. The chapter thus leaves us with questions about why, when the Internet is a potentially powerful leveling tool in the quest for democracy and fairness, does it continue to be defined by egregious sexism and racism?
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé